Capabilities of the Treadmill Test in Modern Cardiological Practice - Olena K. Gogayeva; Liudmyla S. Dzakhoieva (Ukrainian Journal of Cardiovascular Surgery, 2023)
Many publications in recent years have been dedicated to the search for the best preliminary method of diagnosing coronary artery disease (CAD), where the availability of technology and staff experience are the determining factors. According to the National Cardiovascular Data Registry of the American College of Cardiology, 58.4% of patients referred for coronary angiography after functional testing do not have significant coronary artery stenoses. European guidelines for the diagnosis and management of patients with chronic coronary syndrome recommend the use of imaging diagnostic tests instead of exercise electrocardiography for the diagnosis of obstructive CAD.The aim. To analyze the capabilities of the exercise electrocardiography test for patients in modern cardiological practice.Materials and methods. A treadmill test was performed on 406 patients, among whom 317 (78.07%) were men, 89 (21.9%) were women, the mean age was 44.7±17.3 years. The test was carried out according to the Bruce protocol on the Valiant Ergometric Treadmill.Results. The patients were divided into groups depending on the area of diagnostic search: verification of CAD in cardiac pain (n=184); evaluation of the long-term results of cardiac surgery (n=74); visualization of myocardial ischemia in borderline stenoses of coronary arteries (n=4); screening in the presence of additional CAD risk factors (n=49); in the case of heart rhythm disorders in order to decide on further treatment tactics and evaluation of the effectiveness of the antiarrhythmic treatment (n=34); evaluation of the coronary artery in patients with congenital heart defects (n=7); determination of tolerance to physical exertion (n=54). Among the examined patients, there were 48 (11.8%) with positive, 246 (60.5%) with negative, and 112 (27.5%) with doubtful treadmill test. Among 48 patients with a positive treadmill test, myocardial revascularization was performed in 41 (85.4%) cases.Conclusions. Exercise electrocardiography is an affordable tool for diagnostic research which, with its high-quality performance and interpretation, can be an alternative to modern imaging techniques.